Association study with two markers of a human homeogene in infantile autism. Issue 4 (April 1995) - Petit, E; Hérault, J; Martineau, J; Perrot, A; Barthélémy, C; Hameury, L; Sauvage, D; Lelord, G; Müh, J P
Abstract : Epidemiological data and family studies in autism show that there is a genetic susceptibility factor in the aetiology of this syndrome. We carried out an association study in infantile autism. Two markers of the homeogene EN2 involved in cerebellar development were tested in a population of 100 autistic children and in a population of 100 control children. With the MP4 probe showing a PvuII polymorphism, significant differences in the allele frequencies between the two populations were found (chi 2 = 7.99, df = 1, p < 0.01). With the MP5 probe showing an SstI polymorphism, no difference appeared (chi 2 = 1.17, not significant). Several clinical examinations allowed us to characterise the autistic children. Most of them had high scores for autistic behaviour and language disorders but low scores for neurological syndromes. Two children had a significant family history and six children had confirmed syndromes or diseases of genetic origin. Discriminant analysis between clinical and molecular data did not give significant results. These preliminary results must be supported by further analyses of this gene and by studies of its potential involvement in the pathophysiology of the autistic syndrome.